STEAM Learning Model in Madrasah Ibtidaiyah - Ali Kharozim, Muhammad (Universitas Islam Zainul Hasan Genggong, 2024)
This research explores the application of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning model in Madrasah Ibtidaiyah as an innovative strategy to improve the quality of education and 21st century skills. The STEAM model is adapted to integrate science, technology, engineering, arts, and mathematics with religious values and characters relevant to the context of Madrasah Ibtidaiyah. Through this approach, the study aims to evaluate the effectiveness of STEAM in developing critical thinking, creativity and collaboration skills among students, as well as analyzing its impact on the understanding of academic concepts and character building. The results are expected to provide new insights on how to optimize the curriculum in Madrasah Ibtidaiyah to prepare students for global challenges by integrating discipline-based learning and moral values.